"Broken Men" and "Thatcher's Children": Memory and Legacy in Scotland's Coalfields. (7th January 2014) - Perchard, Andrew
Abstract This article explores the legacy of the demise of the deep coal mining industry in Scotland. It places particular emphasis on the cultural scars of this process as witnessed through miners' and managers' memories, positioning these within the context of occupational socialization, conflict, and alienation. The piece explores the enduring importance of these cultural scars in shaping broader collective narratives of decline in Scotland, and how responses were manifest in shifting political outlooks and the emergence (at both a local and national level) of a resurgent nationalism from the early 1960s onward. Drawing on the notion of the "cultural circuit, " the article examines how and why personal experience of the loss of the coal industry informed and conformed to the politics of the miners' union in Scotland, the National Union of Mineworkers Scottish Area (NUMSA). As the article makes clear, the program of closures in the industry has left profound psychological scars in coalfield communities—ones that, like the closure of other major industrial sites, shape a powerful national narrative.